a) [tex] \frac{x}{18a} + \frac{5}{9ax} [/tex]=[tex]\frac{x}{2.9a} + \frac{5}{9ax}=\frac{ x^{2} }{2.9ax} + \frac{2.5}{2.9ax}=\frac{ x^{2} }{18ax} + \frac{10}{18ax}=\frac{ x^{2} +10}{18ax}[/tex]
b) [tex] \frac{9}{ x^{2} -8x+12}+ \frac{4}{ x^{2} -4} = \frac{9}{ (x-2)(x-6)}+ \frac{4}{ (x-2)(x+2)} = \frac{9(x+2)+4(x-6)}{ (x-2)(x-6)(x+2)} \\ =\frac{13x-6}{ (x-2)(x-6)(x+2)}[/tex]
c)[tex] \frac{ 3x^{2}-2 }{ x^{2} -8x+12} - \frac{3}{5x-30} =\frac{ 3x^{2}-2 }{ (x-2)(x-6)} - \frac{3}{5(x-6)} \\ =\frac{ 5(3x^{2}-2)-3(x-2) }{ (x-2)(x-6)} =\frac{ 15x^{2}-10-3x+6 }{ (x-2)(x-6)} \\ =\frac{ 15x^{2}-3x-4 }{ (x-2)(x-6)}[/tex]
d) [tex] \frac{2x-3}{ x^{2} -x-6}+ \frac{6}{x-3} = \frac{2x-3}{ (x-3)(x+2)}+ \frac{6}{x-3} \\ =\frac{(2x-3)+6(x+2)}{ (x-3)(x+2)}==\frac{8x+9}{ (x-3)(x+2)}[/tex]